"Asking, Learning, Seeking Out": An Exploration of Data Literacy for Teaching. Issue 2 (2nd April 2020) - Beck, Jori S.; Morgan, Joseph John; Brown, Nancy; Whitesides, Heather; Riddle, Derek R.
Abstract: The current study explored preservice and inservice teachers' perspectives on data literacy for teaching. Semi-structured interviews were employed with 12 teacher candidates in elementary and special education. The findings revealed participants' misconceptions regarding formative and summative data; their understanding of the value of formative data; perceptions of challenges related to data literacy for teaching including time, making sense of data, and reliability and validity; and candidates' preferences for authentic data literacy instruction.